Ectoparasite Fauna of Rodents and Shrews with Their Spatial, Temporal, and Dispersal along a Degradation Gradient in Mabira Central Forest Reserve - Waswa Sadic Babyesiza; Joseph Mpagi; James Ssuuna; Sisiria Akoth; Abdul Katakweba (Journal of Parasitology Research)
Ectoparasites like fleas, mites, and ticks that are key carriers of harmful pathogens such as viruses, bacteria, cestodes, and nematodes live on rodents and shrews. It should be noted that rodents’ ecological adaptability makes them suitable as parasite hosts. The main objective of the study was to determine the ectoparasite assemblages in rodents and shrews along a degradation gradient, while comparing infestation levels in different habitats with varying levels of degradation. The study was conducted in Mabira Central Forest Reserve. Ectoparasites were collected following rodent and shrew removal trapping which was done using Sherman’s traps set along transects of 200 meters in three habitat strata that included adjacent forest habitats, degraded forest edge, and regenerating forest interior. Data was collected intermittently with a break every two months for one year from November 2018 to December 2019. A total of 1411 rodents and shrews were collected, yielding a total of 5692 ectoparasites from 22 host species (17 rodents and 5 shrews). The most prevalent group of ectoparasites was mites followed by fleas, lice, ticks, and earwig. Ectoparasite prevalence significantly differed depending on hosts species (P=0.001) and host age (P=0.022), but not host sex (P=0.78), while mean infestation significantly varied basing on host species (P=0.001), host sex (P=0.001), season (P=0.001), and habitat (P=0.001). Prevalence (P=0.001) and mean infestation (P=0.001) significantly varied across studied habitats. The study has emphasized the significance of Praomys jacksoni and Hylomyscus stella as significant hosts for mites and S. congicus as a significant host for fleas. Additionally, environment and host characteristics have a bearing on prevalence and infestation of ectoparasites with habitat degradation playing a significant role in the occurrence of ectoparasites, thereby emphasizing its contribution to zoonotic outbreaks.